Monitoring Sistem Ketersediaan dan Pengontrolan Pengisisan Air Secara Otomatis Pada Gedung Perkantoran Berbasis Mikrokontroler - Dodon Yendri; Desta Yolanda; Rezy Pratiwi (Universitas Andalas, 2020)
Employees who work in offices absolutely need water, for example to wash hands, to defecate, or other household needs. Water availability must be a concern of managers. But in fact, many officers pay less attention for this. They let a lot of water flows from the tank or reservoir that makes important water resources are wasted. This study aims to regulate the usage of water in office buildings so that water needs for employees are always met. The system was built by three tanks, one tank as the main water source called the central tank and two tanks as a reservoir of water that will be consumed by employees called tank1 and tank2. To measure the water level in the tank, it will use an ultrasonic sensor. If the water in the central tank has reached the minimum capacity length from the surface of the water to the sensor (≥ 20 cm), the tank manager will receives an SMS that indicates the water in the central tank is not available and needs to be refill. Tank 1 and tank 2 are filled automatically by activating the pump and opening the solenoid valve when the water is less than the maximum limit set (> 5 cm). The results showed that the system was able to send an SMS to the tank manager when the water level had reached the minimum limit with an 7.39 seconds of average delivery time. Tank 1 and tank 2 can be returned off when the water level reaches the 5 cm limit. The average success rate of filling water in tank1 was 98.46% and tank2 was 97.32%.